On some types of propermutable subgroups and their generalizations in finite groups - Pypka, A.A.; Storozhenko, D.Yu. (Reports of the National Academy of Sciences of Ukraine, 2017)
We found some specific examples of propermutable and S-propermutable subgroups in finite groups. In particular, we have given the positive answer to the question 18.91 (a) from the Kourovka Notebook.